2010
DOI: 10.1302/0301-620x.92b12.23366
|View full text |Cite
|
Sign up to set email alerts
|

Experimental osteoarthritis induced by surgical realignment of the patella in BALB/c mice

Abstract: The patellofemoral joint is an important source of symptoms in osteoarthritis of the knee. We have used a newly designed surgical model of patellar strengthening to induce osteoarthritis in BALB/c mice and to establish markers by investigating the relationship between osteoarthritis and synovial levels of matrix metalloproteinases (MMPs). Osteoarthritis was induced by using this microsurgical technique under direct vision without involving the cavity of the knee. Degeneration of cartilage was assessed by the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Another positive regulator of inflammatory response found in the gene profile was Aif1, which is known to be highly expressed in synovial tissues of rheumatoid arthritis patients 32 . In addition, macrophages in response to cartilage fragments stimulation expressed proteolytic enzymes including matrix metalloproteinases Mmp9 and Mmp14, and disintegrin and metalloproteinase domain-containing protein 17 (Adam17), which are known to be involved in demineralization of bone, degradation of components of the extracellular matrix and digestion of matrix proteins [33][34][35][36] . Not surprisingly, our bioinformatic analysis revealed that the upregulated genes in stimulated macrophages were significantly enriched in rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Another positive regulator of inflammatory response found in the gene profile was Aif1, which is known to be highly expressed in synovial tissues of rheumatoid arthritis patients 32 . In addition, macrophages in response to cartilage fragments stimulation expressed proteolytic enzymes including matrix metalloproteinases Mmp9 and Mmp14, and disintegrin and metalloproteinase domain-containing protein 17 (Adam17), which are known to be involved in demineralization of bone, degradation of components of the extracellular matrix and digestion of matrix proteins [33][34][35][36] . Not surprisingly, our bioinformatic analysis revealed that the upregulated genes in stimulated macrophages were significantly enriched in rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Egloff et al investigated the effect of muscle weakness using surgical denervation and intramuscular drug injection on the progression of OA, and exhibited an increase in the OARSI score of the PF joint at 3 months postoperatively [ 34 ]. Chia et al used a newly designed surgical model to induce OA in mice and stated that the PF joint showed evidence of mild OA at 8 weeks and further degeneration at 12 weeks after surgery [ 35 ]. Though these studies were able to report these changes in PFOA, the studies reported findings that had problems with temporal, not sequential, histopathological evaluation and the reproduction of only mild OA or OA during the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…8 COMP, MMP-3, and MMP-9 synovial fluid levels also increased in mice after acute joint injury induced by intraarticular fracture. 38,39 In a study of Porta et al, 40 the endocannabinoids anandamide (AEA) and 2-arachidonoylglycerol (2-AG) did not modify serum levels of MIA and control groups.…”
Section: Micementioning
confidence: 95%